Epoxy resin: coffee table from Casuarina equisetifolia slab / Imaduddin Khairul Aznam - Khairul Aznam, Imaduddin (2023)
In recent years, coffee tables have grown far too plain on the furniture market. They lack character because they are generally composed of laminated particleboard and have a plain design. Most furniture producers care about the type of wood that goes into their creations, perhaps to draw attention to the priciest piece of wood. This article's goal is to put out a suggestion for how to construct a coffee table made of epoxy resin. This study is carried out to achieve the required objectives which to design an epoxy resin coffee table by using Casuarina equisetifolia slabs and the combination epoxy resin and metal, to produce an epoxy resin coffee table by using Casuarina equisetifolia slabs and the combination epoxy resin and metal and also to evaluate the user’s satisfaction on knowledge, materials, and the design of the epoxy resin coffee table through questionnaire survey. Materials and production methods for the epoxy resin coffee table are explored. This approach combines the product design and production processes. Casuarina equisetifolia slab for the surface and aluminium for the table legs make up the coffee table's primary materials. The Wood Industry Workshop, UiTM Pahang provides the wood slab and epoxy resin. While metal table leg is customized. A coffee table is made to stand out from other, seemingly identical coffee tables and attract customers due of its distinctive design and look. These coffee tables fully persuade clients to desire one in their home because of its distinctive style.